The Effectiveness of Cognitive-Behavioral Therapy on Ambiguity Tolerance in Adolescents with Social Anxiety - Alijani Baei, Tabassom; Mirzaian, Bahram; Norouzi, Asghar (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to examine the effectiveness of cognitive-behavioral therapy (CBT) on ambiguity tolerance in adolescents with social anxiety disorder. Methodology: The research method was quasi-experimental, employing a pretest-posttest design with a control group and a one-month follow-up phase. The statistical population consisted of all adolescents diagnosed with social anxiety disorder who attended eight counseling centers in Babol city during the spring of 2024. Initially, the Connor Anxiety Questionnaire (2000) was distributed among all participants, and 30 individuals scoring between 16 and 25 (the questionnaire's cutoff point) were selected through convenience sampling. These participants were then randomly assigned to either the experimental or control group. Data were collected using the second version of the McLain Ambiguity Tolerance Questionnaire (1993) and the Connor Social Anxiety Questionnaire (1969). The experimental group underwent CBT based on Beck’s (1998) manual, which was conducted in 12 sessions, each lasting 90 minutes. The intervention was solely applied to the experimental group, with no intervention for the control group. Data were analyzed using repeated measures analysis via SPSS-18 software. Findings: The findings indicated a significant difference in pretest and posttest scores between the experimental and control groups regarding ambiguity tolerance in adolescents with social anxiety disorder (P ≤ 0.01). Overall, CBT is effective in enhancing ambiguity tolerance in adolescents with social anxiety disorder (P ≤ 0.01). Conclusion: Given the results of this study, the role of CBT in facilitating changes in ambiguity tolerance has important therapeutic implications.